Comparative performance evaluation of anodic materials for electro-kinetic removal of Lead (II) from contaminated clay soil. Issue 1 (2nd January 2020) - Mu'azu, Nuhu Dalhat; Essa, Mohammed H.
ABSTRACT: A comparative cost-effectiveness performance evaluation of graphite, glassy carbon, irrudium coated titanium and titanium anodes during electro-kinetic removal (EKR) of Pb(II) ions from contaminated clay soil was investigated. The influences of catholyte concentration (0.2-1N), spacing between electrodes (15-25 cm), treatment time (1-3 weeks) and distance from anode(5-15 cm) on Pb (II) residual concentration were evaluated and optimized using Response Surface Methodology. The relative contribution of the operating conditions follows the order; treatment time > distance from anode > electrode spacing > catholyte concentration. All the anodes yielded high Pb(II) removal with graphite exhibiting slower performance. The electro-osmotic volumes collected at the catholyte compartments suggest electro-osmosis as dominant removal mechanism while Ir-coated titanium exerted the highest electroosmotic mobility coefficients of 0.0054 cm 3 s -1, 4.98 x 10 -5  cm 2 V -1 s -1  and 0.00208 cm 2 A -1 s -1 . The least energy expenditure of $46.21per kWh, $0.13 per kWhm -3 and $49.74 per kWh.m -3 mg -1 was attributed to graphite, followed by titanium and then Ir-coated titanium. The most exorbitant glassy carbon considerably exhibited the least performance with $2134.64 per kWh, $6.15 per kWhm -3  and $2094.8 per kWh.m -3 mg -1 . This study underscores the relevance of taking anodic materials cost into considerations for better evaluation of EKR effectiveness for remediation of heavy metals contaminated-soils.